Serum ferritin and anemia in trained female athletes - Ashenden, M. J.; Martin, D. T.; Dobson, G. P.; Mackintosh, C.; Hahn, A. G. (International Journal of Sport Nutrition and Exercise Metabolism, 1998)
Hematological data collected during 6 years at the Australian Institute of Sport were reviewed to quantify changes in serum ferritin concentration associated with training and to establish whether decrements in serum ferritin were associated with any change in hemoglobin concentration, mean corpuscular volume, or mean corpuscular hemoglobin concentration.